Community imaginaries, participation and acceptance of renewable energy projects – substituting the quicksand of development with rocky fundamentals - Seroala Tsoeu-Ntokoane; Thuso Donald Mosabala; Moeketsi Kali; Xavier Lemaire (Cogent Social Sciences)
Community participation could contribute to sustaining energy projects, however some projects underestimate the value of meaningful project host communities’ involvement in decision-making. Rural community energy development projects in Lesotho often assume a top-down development-driven approach void of communities’ perspectives and desires. This study investigates opportunities Lesotho’s renewable energy projects, either led by communities or the government, provide. The authors draw from qualitative research to examine two cases, Semonkong and Motete’s participatory approaches. This study determined the magnitude of community participation in the two projects, from their initiation to the level of community participation in decision-making and implementation. The findings posit that community participation in both projects differs from minimal to no participation. They further revealed a blurry picture of community acceptance of the project where participation was relatively lower, thus bringing project sustainability into question. The Lesotho Electric Company deprived the Semonkong community the opportunity to participate in the decisions of the Semonkong mini-grid. In contrast, the Motete project consortium allowed a modicum of community participation hence higher social acceptance prospects. The study revealed that tensions, conflicts, and protests are implications associated with lack of community participation in the project of Semonkong. The sustainability of projects is dependent on the extent of the host communities’ involvement, acceptance, and trust. This study recommends community engagement for hammering and forging project acceptability and sustainability.